Michel Desjardins: An Angel of Academia - Andrus, Erica Hurwitz (Religious studies and theology, 2019)
This essay reflects on the personal experiences of the author as a student in the M.A. in Religion and Culture program at Wilfrid Laurier University in the 1990s. Erica Hurwitz Andrus remembers how Michel’s classes became an important part of her intellectual growth as a scholar and ultimately a teacher. He demonstrated the use of theory to critique past scholarship in Religious Studies, the ways that popular culture can engage with religion and how that engagement provides a critique for the secularization theory of the day, and finally how established scholars can be mentors and partners to students and junior colleagues. All of these lessons continue to inform her work writing and teaching in the Religion Department at the University of Vermont.